2015
DOI: 10.4085/1062-6050-49.3.94
|View full text |Cite
|
Sign up to set email alerts
|

Balance Training and Center-of-Pressure Location in Participants With Chronic Ankle Instability

Abstract: Context: Chronic ankle instability (CAI) occurs in some people after a lateral ankle sprain and often results in residual feelings of instability and episodes of the ankle's giving way. Compared with healthy people, patients with CAI demonstrated poor postural control and used a more anteriorly and laterally positioned center of pressure (COP) during a single-limb staticbalance task on a force plate. Balance training is an effective means of altering traditional COP measures; however, whether the overall locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 41 publications
0
52
0
8
Order By: Relevance
“…These range from simple progressive strength [12][13][14][15] or balance [16][17][18][19] protocols to multicomponent (strength, balance, ROM) rehabilitation 20,21 approaches. These functional rehabilitation protocols effectively improve strength, balance, and self-reported function [12][13][14][15]19,[21][22][23][24][25] ; however, few researchers have assessed the improvements in functional performance that include power and agility. Functional activity is defined as dynamic, closed kinetic chain activity other than quiet standing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These range from simple progressive strength [12][13][14][15] or balance [16][17][18][19] protocols to multicomponent (strength, balance, ROM) rehabilitation 20,21 approaches. These functional rehabilitation protocols effectively improve strength, balance, and self-reported function [12][13][14][15]19,[21][22][23][24][25] ; however, few researchers have assessed the improvements in functional performance that include power and agility. Functional activity is defined as dynamic, closed kinetic chain activity other than quiet standing.…”
mentioning
confidence: 99%
“…13,25 Therefore, strength training alone may be insufficient to improve functional outcomes similar to the movements that occur more often during sport and physical activity. Balancetraining protocols (BTPs) 19,23 and resistance-band protocols (RBPs) have been shown to improve strength 12,13,15 and postural-control 18 variables, respectively; however, they have not been examined in the same study.…”
mentioning
confidence: 99%
“…Several studies reported positive effects of balance training on static and dynamic balance (Granacher, Mueulbauer, Doerflinger, & Strohmeier, 2011;Yu & Yang, 2012;Mettler et al, 2015;Çankaya et al, 2015;Baccouch, Rebai, & Sahli, 2015;Zemkova et al, 2017;Hamed, Bohm, Mersmann, & Arampatzis, 2017;Simpson et al, 2017). More specifically, static balance exercises are suggested as more effective in balance performance than dynamic balance exercises (Erdoğan et al, 2017).…”
Section: Study Limitations and Implications For Future Assessmentmentioning
confidence: 99%
“…(Kaminski et al, 2003;Kidgell et al, 2007;McKeon et al, 2008;Cha & Kim, 2009;Doherty et al, 2017). 여러 선행연구들은 불안정한 지면에 서의 균형 운동이 근력, 평형성, 자세 진동 등에 긍정적인 영향을 주어 근신경계의 통합에 효과적임을 보고하였다 (Richie, 2001;Mettler et al, 2015). Mckenzie et al(1985) (Schlosser, 1997).…”
unclassified